Solid-State FTIR Spectroscopic Study of Two Binary Mixtures: Cefepime-Metronidazole and Cefoperazone-Sulbactam. (3rd March 2017) - Ali, Hassan Refat H.; Ali, Ramadan; Batakoushy, Hany A.; Derayea, Sayed M.
Abstract : The structural information of the pharmaceuticals and insights on the modes of molecular interactions are very important aspects in drug development. In this work, two cephalosporins and antimicrobial combinations, cefepime-metronidazole and cefoperazone-sulbactam, were studied in the solid state using FTIR spectroscopy for the first time. Quantitation of the studied drugs and their binary mixtures was performed by integrating the peak areas of the characteristic well-resolved bands: υ (C=O) band at 1773 cm −1 for cefepime and ring torsion band at 826 cm −1 for metronidazole and υ (C=O) band at 1715 cm −1 for cefoperazone and ring torsion band at 1124 cm −1 for sulbactam. The results of this work were compared with the relevant spectrophotometric reported methods. This study provides data that can be used for the preparative process monitoring of the studied drugs in various dosage forms.